Partisipasi Masyarakat Desa Jungutbatu Di Daya Tarik Wisata Mangrove Tour, Nusa Lembongan, Kecamatan Nusa Penida, Kabupaten Klungkung - Pande Gede Kusuma Putra; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
The Village of Jugutbatu has mangrove forest which is used as a tourist attraction. Mangrove forest itself has a function to minimize abrasion and tidal wave. Utilization of the attraction is inseparable from the participation of Jungutbatu villagers so this study aims to see the form of participation of Jungutbatu villagers in mangrove tour This research uses observation, interview, and documentation techniques. This research uses qualitative data. Data source used is primary and secondary data source. Data analysis techniques in the form of narrative data exposure Tourist attraction in newly discovered mangrove forest. Then the community began to plunge into the field of tourism by estabilishing mangrove tour organization sari segara serving mangrove tour services and making various tourism services such as restaurants, souvenirs, and alternative services around mangrove forests such as canoes, and standard paddle. Finally, public awareness to preserve the environment to create sustainable tourism Keywords : Mangrove Tour, Participation, Local Community